A single‐centre experience of Roux‐en‐Y enteric drainage for pancreas transplantation. (2nd March 2017) - Amin, Irum; Butler, Andrew J.; Defries, Gail; Russell, Neil K.; Harper, Simon J. F.; Jah, Asif; Saeb‐Parsy, Kourosh; Pettigrew, Gavin J.; Watson, Christopher J. E.
Summary: Exocrine drainage following pancreas transplantation can be achieved by drainage into the bladder or bowel, the latter typically by direct duodeno‐jejunostomy; the use of Roux‐en‐Y enteric drainage is uncommon. We report a retrospective analysis of a single‐centre experience of Roux‐en‐Y enteric drainage following pancreas transplantation. Over a 14‐year period (2001–2015), 204 consecutive adult pancreas transplants were performed (96.6% simultaneous pancreas and kidney transplants), of which 26.0% were from donors after circulatory death (DCD). During a median follow‐up of 67 months (range 13–183 months), 14 (6.9%) recipients experienced complications related to their enteric drainage. Complications during follow‐up included early enteric anastomotic haemorrhage (five patients), non‐anastomotic enteric bleeding (one patient), small bowel obstruction (four patients) and graft duodenal perforation (two within 6 weeks, five beyond 12 months). No recipient lost their graft as a direct result of complications related to enteric drainage. Patient and pancreas graft survival at 1 year was 99.0% and 94.0% and at 5 years 91.3% and 84.9%, respectively. We conclude that Roux‐en‐Y enteric drainage following pancreas transplantation is a safe and effective procedure and facilitates graft salvage in the event of graft duodenal perforation.